2008
DOI: 10.1039/b804485f
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerized diffusion-defined polyacrylamide gradient gels for on-chip protein sizing

Abstract: We report on a facile diffusion-based photopatterning technique for generating linear and non-linear decreasing pore-size gradients in cross-linked polyacrylamide gels. Diffusion of low viscosity polymer precursor solutions and a two-step photopatterning process were used to define the decreasing pore-size gradient gels in a microfluidic format, thus eliminating the need for controlled mixing and delivery of polymer precursor solutions. We present an analytical model of the non-steady state diffusion process a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 31 publications
(20 reference statements)
0
50
0
Order By: Relevance
“…S3), with resolution similar to conventional slab-gel Western blotting. Although only uniform pore-size gels are studied here, the PACTgel pore size distributions are tunable, thus allowing enhanced resolution over specific weight ranges of interest (22)(23)(24). Importantly, the first sizing stage is observed to complete in compact 3-mm separation distances in separation times of ∼60 s. Consequently, the duration of the sizing step in μWestern blotting compares favorably to the 40-90 min required for macroscale protein sizing.…”
Section: Resultsmentioning
confidence: 90%
“…S3), with resolution similar to conventional slab-gel Western blotting. Although only uniform pore-size gels are studied here, the PACTgel pore size distributions are tunable, thus allowing enhanced resolution over specific weight ranges of interest (22)(23)(24). Importantly, the first sizing stage is observed to complete in compact 3-mm separation distances in separation times of ∼60 s. Consequently, the duration of the sizing step in μWestern blotting compares favorably to the 40-90 min required for macroscale protein sizing.…”
Section: Resultsmentioning
confidence: 90%
“…Recently, diverse techniques have been utilized for the systematic study of the effects of a substrate's stiffness gradient on cell behaviors. They include diffusion [21], controlled dipping into crosslinking solution [22], microfluidics/photopolymerization [23], gradient mask/photopolymerization [24], convection-alternating flow/photopolymerization [25], photopolymerization using a gradually darkening mask [26], photopolymerization using a sliding mask [16,27], temperature gradients during crosslinking [28], and controlling the height of the substrate [29]. However, the toxicity from residual monomers, precursors, photoinitiators, and crosslinkers [30e33]; different surface chemistry from different densities of crosslinkers along the gradient [22]; relatively narrow ranges of stiffness gradient [29]; and the complexity of fabrication processes are also considered as potential limitations of conventional systems.…”
Section: Introductionmentioning
confidence: 99%
“…This wok provides inspiration for the design of unique tissue engineering scaffolds based on the gradient hydrogel network by in situ encapsulation of cells. Herr et al [69] reported on the fabrication of gradient polyacrylamide with diminishing pore sizes by using diffusion-based photopatterning method. Compared with the traditional method in the fabrication of pore-size gradients [70], this approach is much easy and displays great importance for microfluidic electrophoresis [71].…”
Section: A N U S C R I P Tmentioning
confidence: 99%